Tourism In OIC Countries: A Review Based On Scopus Database - Abrista Devi (Halal Tourism and Pilgrimage, 2023)
This study aims to look at the development of research on "Tourism in OIC" worldwide and research plans that can be carried out based on published journals with this theme. This study used a qualitative method with a bibliometric analysis approach. The data used is secondary data with the theme "Tourism in OIC" from the Scopus database with a total of 655 journal articles. Then, the data is processed and analyzed using the VosViewer application to know the bibliometric map of the development of "Tourism in OIC" research worldwide. The results of the study found that in the bibliometric author mapping, the authors who published the most research on the theme "Tourism in OIC" were Henderson JC; Jalilvand MR; Samiei N; Ahmed F.; Haque A.; Abdullah K.; Razali SS; Michael Hall C.; Prayag G; and Cusack CM Furthermore, based on the bibliometric keyword mapping, there are 3 clusters that can become research lines with topics related to Challenges in the Development of Tourism Amidst the Covid-19 in OIC, Halal Tourism and its Impact on Muslim Tourists' Satisfaction in OIC and Community Engagement and Cultural Hospitality in OIC, and for the words most used are destination, development, Muslim tourist, and challenge.